A informação sob a perspectiva de Luciano Floridi: fake news como um caso prático - Carvalho, Fábio Rodrigo Oliveira (Universidade do Vale do Rio dos Sinos, 2021)
Advances in technology have meant that significant changes in different fields of science have had an impact on society, such as the ease of communication between individuals, between companies, as well as by government agencies. These changes are perceived by the variation of time and methods of information propagation. Information, in turn, does not seem to have taken the lead in this medium, supporting new technologies, it is as if information were a naturally present part of a communication. But, information is not only supported by technology, but without information technology would not work, so information and technology coexist in a symbiotic way. However, it is necessary to make a distinction of what information is since it is the subject of this research. The general objective is to understand what this coexistence with technology means and from which moral consequences flow. Therefore, it is also necessary to deepen the knowledge in Philosophy of Information to understand this connection between information and technology, as well as to understand the field of action of Information Ethics, which allows theorizing considering new dilemmas in this technological context and finally, to choose a social phenomenon that portrays this blunt reality. Then, a bibliographic research about the works of the Italian philosopher Luciano Floridi was made, as well as other authors, which also makes it a research of exploratory methodology, and a qualitative approach. Given this, it appears that the definition of information is very complex, comprising practically all the author's theory of the Philosophy of Information. The fact that there are new ethical issues that lack an appropriate conceptual analysis regarding the context of the new dilemmas that arise is also faced, and, certainly, that the choice of fake news as a current phenomenon is adequate, giving visibility to one of the several challenges that are being imposed by the approximation between technology and information. As a result, it is concluded that the definition of information that best adapts to this technological evolution, according to Floridi, is semantic information. This definition will reflect on his ethical theory, appropriating the concept of infocentric ethics, which establishes an informational environment that is inhabited by information agents. In conclusion, the phenomenon of fake news demonstrated that a possible solution to this social problem goes beyond technological, epistemological and argumentative issues, invading areas of the science of human behavior, due to the persuasive character of this type of news.
Keywords: Ética da informação; Filosofia da informação; Tecnologia; Fake news; Information ethics; Philosophy of information; Technology; ACCNPQ::Ciências Humanas::Filosofia